Editorial (2018)
On April 24 we had the pleasure of celebrating 50 years of Análisis: Revista Colombiana de Humanidades, within the framework of the Bogotá International Book Fair (2018). The academic event had the participation of Friar Alberto Ramírez, O. P., director of the Department of Humanities and Comprehensive Training; Professor Roberto Salazar Ramos, guest speaker, and some editors of the scientific journals of the University of Santo Tomás. Highlighting the role of Análisis and the serial publications in the dissemination of specialized knowledge was a valuable objective achieved before the crowded auditorium that accompanied us in the room Jorge Isaacs, of Corferias.Founded in 1968 and a pioneer in the publications of the University, the journal Análisis has contributed in different ways to the field of knowledge during these 50 years: it has been an important channel for the dissemination of Latin American philosophy, research on language, art and literature. Its pages also host discussions on bioethics, discourse analysis, historiography, cultural studies, and, of course, the humanities. Because of its long history, being a hinge journal between the 20th and the 21st centuries, it is, in the words of Professor Roberto Salazar, a testimony of the era: its 93 numbers include copious interpretations of Colombian events.Precisely, in the prologue to the first issue of Análisis, at that time journal Santo Tomas, Father Friar Luis J. Torres OP, University chancellor in the seventies, affirms that the journal participated in the essential university project: the promotion of arts, science and research in Colombia, key tools, in his opinion, to achieve happiness. For this reason, Análisis establishes, since that moment, a particular connection with human development and, in fact, is destined, as Professor Salazar points out, “to keep Thomist thought in force as a way of interpreting the convulsive century in which we live”.In this issue 93, Humanist convergences: peace, culture, religion and philosophy, after celebrating 50 years of the journal, we want to show the variety of contributions that converge here. The two initial articles are framed in the constitution of a peaceful coexistence from the recognition of intersubjective relationships, the multiple forms of violence and the problematization of “liberal peace”: the first explores interpersonal conflict and the development of argumentative skills as reasonable opportunities in situations that put coexistence at risk; the second enquires for the relevance of decolonial theory and praxis in the current situation of the country.Analyze culture around the industry, humanism and forms of symbolic production is the axis of the following two papers: one of the articles proposes to explain, through the concept of cultural capital, the relationship between the cultural expressions of society and its production conditions, the other sees in the humanist culture, which defends freedom, a way to overcome alienation.To broaden the spectrum on religious studies, the following paper presents an interesting dialogue between the theories about native religions and popular theology, which relies on key implications for the experience of the popular and the philosophy of liberation. In that same editorial line, the concomitant research article analyzes the disputes surrounding the image of the Holy Ecce-Homo, we will notice, then, a suggestive dispute between the State and the Church, as well as between the secular and the regular clergy.The last three articles that make up this issue address philosophical reflections in context that allow us to speak, think and act in our time. The first revolves around the question about the role of the philosopher in today's world, while the second aims to analyze the process of decomposition of contemporary advanced societies in the framework of the modernity-postmodernity transition. The final piece of the section deals with the desire as a productive power of the reality of individuals, which plays a fundamental role in the eager race for personal success and the unstoppable logic of the market. To close, we present a translation to Spanish, prepared by Dolores Sánchez, about an academic article by Robert Vinten on the great philosopher, linguist and mathematician Ludwig Wittgenstein.